Impact of sand and dust storms on mortality in Jinan City, China - Shen, Chaofan; Li, Mingjun; Wang, Qingchang; Luan, Jinjiao; Si, Jiliang; Cui, Liangliang (Frontiers in Public Health, 2025)
BackgroundSand and dust storms (SDSs) cause considerable health risks worldwide. China is a country seriously affected by SDSs, however only few studies researched the risk of SDS in China. The insufficient evidence on SDS hampers effective measures to mitigate its harm.ObjectiveTo reveal the mortality risks associated with SDSs in Jinan City and identify sensitive populations vulnerable to these events.MethodsFor this time-stratified case-crossover study, we collected daily data on all-cause, circulatory, and respiratory deaths, as well as air pollution and meteorological information from Jinan City in China between January 1, 2013, and November 30, 2022. We initially utilized a time-stratified case-crossover design and logistic regression model to examine the short-term relationship between SDSs and mortality risks, adjusting for specific variables such as mean temperature, humidity, wind speeds, and holidays. Subsequently, we conducted stratified analyses by age, gender, and season.ResultsA total of 53 SDSs were observed, lasting for 88 days during the study period, which accounted for 2% of the study period. The excess mortality risks associated with SDSs were 13% (95% CI: 4–22%), 4% (95% CI: 1–8%), and 3% (95% CI: 1–6%) for respiratory, circulatory, and all-cause death, respectively. Females and people over 65 years of age are vulnerable to respiratory deaths caused by SDSs.ConclusionShort-term exposure to SDSs caused the significantly elevated risks of respiratory, circulatory and all-cause death. Females and individuals over the age of 65 are particularly vulnerable to the effects of SDSs.